2017
DOI: 10.1186/s12905-017-0487-7
|View full text |Cite
|
Sign up to set email alerts
|

Obesity associates with vasomotor symptoms in postmenopause but with physical symptoms in perimenopause: a cross-sectional study

Abstract: BackgroundMiddle-aged women experience various menopausal symptoms during the menopause. These symptoms can affect their quality of life and health. Several epidemiological studies reported that obesity associates with menopausal symptoms. The aim of this cross-sectional study was to examine the associations between obesity and multiple menopausal symptoms at different stages of menopause in middle-aged Korean women.MethodsThe study population included women aged 44–56 years who visited a tertiary referral hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 33 publications
5
29
0
2
Order By: Relevance
“…Our study was consistent with previous studies [5][6][7]. Overweight and obesity factors are associated with the occurrence of climacteric symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study was consistent with previous studies [5][6][7]. Overweight and obesity factors are associated with the occurrence of climacteric symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have identified that the incidence and severity of climacteric symptoms are associated with various factors, including physiological factors (i.e., reproductive hormones and genetics), sociocultural characteristics (i.e., country, race, and age), health conditions (i.e., chronic disease, overweight, or obesity), and lifestyle (i.e., diet, physical activity, smoking, and alcohol drinking) [3][4][5]. Among the various factors, being overweight or obese is a critical influential factor in distressful climacteric symptoms [5][6][7]. When finding data from SWAN (Study of Women's Health across the Nation), women with a higher BMI (body mass index) showed an increasing incidence or severity of climacteric symptoms when compared with those with a lower BMI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many epidemiological studies revealed the association between the menopausal symptoms and obesity (Koo et al 2017). During perimenopause or postmenopause, the occurrence of low to severe symptoms is positively connected with overweight/weight (Sayón-Orea et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Women experience different menopausal symptoms during the menopausal period. These symptoms can influence their personal satisfaction and well-being (Koo et al 2017). Women's physical and mental ill-health, for example, anxiety and depression symptoms, hypertension, palpitations, osteoarthritis, hot flushes, and urogenital health shows an increment around the ages 45-65 years (Rindner et al 2017).…”
Section: Introductionmentioning
confidence: 99%